PERILAKU MASYARAKAT DALAM PELESTARIAN HUTAN RAKYAT DI DESA DANGIANG, KECAMATAN CILAWU, KABUPATEN GARUT, PROVINSI JAWA BARAT - Awalludin, Rully Ahmad; Salampessy, Messalina L; Supriono, Bambang (Universitas Nusa Bangsa, 2017)
The existence of the community forest in Dangiang Village, Cilawu District, Garut Regency, has supported efforts to conserve forests that are a buffer for people's lives. Sustainable community forest management is influenced by community behavior, as well as factors that support and hinder community efforts in preserving community forests. This study aims to examine the behavior of the community in an effort to preserve community forests and their supporting and inhibiting factors. The research method used is descriptive method with a qualitative approach. The results of the study show that people's behavior is related to aspects of perception, participation, policy, cooperation, women's role, and cultural values / norms; Among them is maintaining the sustainability of community forests by planting, maintaining, and not carrying out activities that damage the forest. The community participates actively in the conservation activities. The supporting factors are the existence of local wisdom, active roles and community collaboration with stakeholders. The inhibiting factor is the economic function of the community forest which is still lacking, human resources are still low, and the accessibility of the area is inadequate. Utilization of community forest potential can increase community income through timber certification, identification of community forest products, increase collaboration between communities and stakeholders, and improve product yields in community forest areas.Â